2021
DOI: 10.3390/molecules26082279
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot-Scale Supercritical Carbon Dioxide Extraction to Valorize Colombian Mango Seed Kernel

Abstract: Colombian mango production, which exceeded 261,000 t in 2020, generates about 40% of the whole fruit as solid waste, of which more than 50% are seed kernels (over 52,000 t solid by-product); though none is currently used for commercial purposes. This study reports the results of the supercritical carbon dioxide (scCO2) extraction of an oil rich in essential fatty acids (EFAs) from revalorized mango seed kernels and the optimization of the process by the Response Surface Methodology (RSM). In pilot-scale scCO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…scCO 2 compared to Soxhlet presents several advantages such as shorter extraction times, low environmental impact, and non-toxicity, which makes it suitable for the industry application and guarantees clean extracted products. This fact does not represent a concern in future applications since several studies have already demonstrated that the lipid extraction yield obtained by Soxhlet and scCO 2 was quite similar [28,29,45]. Nevertheless, at the laboratory scale, the Soxhlet extraction procedure remains the most available to be used for this purpose and obtain preliminary chemical information about the extracts.…”
Section: Lipid Extraction Yield and Fatty Acids Profile And Functiona...mentioning
confidence: 99%
See 1 more Smart Citation
“…scCO 2 compared to Soxhlet presents several advantages such as shorter extraction times, low environmental impact, and non-toxicity, which makes it suitable for the industry application and guarantees clean extracted products. This fact does not represent a concern in future applications since several studies have already demonstrated that the lipid extraction yield obtained by Soxhlet and scCO 2 was quite similar [28,29,45]. Nevertheless, at the laboratory scale, the Soxhlet extraction procedure remains the most available to be used for this purpose and obtain preliminary chemical information about the extracts.…”
Section: Lipid Extraction Yield and Fatty Acids Profile And Functiona...mentioning
confidence: 99%
“…There are several extraction techniques and analytical approaches reported for the assessment of FAs in food by-products. Usually, the lipid fractions are extracted using different organic solvents and mixture of it (e.g., methanol, ether) [24][25][26], Soxhlet [27,28], and supercritical fluid extraction [28,29]. Regarding analytical approaches, infrared spec-troscopy, capillary electrophoresis, liquid (LC), and gas chromatography (GC) have been reported in the determination of FAs profile [30].…”
Section: Introductionmentioning
confidence: 99%
“…Colombia's mango production surpassed 300,000 metric tons in 2021, indicating that the country's mango solid waste capacity exceeded roughly 156,000 metric tons last year. As much as 78,000 tons of this residue were peels, none of which are currently used commercially in Colombia [32]. High-intensity ultrasound-assisted extraction (HIUAE) is extensively used in the food industry due to its capability to process with low energy consumption, short times, low solvent usage, high safety of the operators, and high extraction yields.…”
Section: Discussionmentioning
confidence: 99%
“… Schematic of the supercritical CO 2 extraction setup. Reproduced from [ 185 ] with permission (open access, Attribution 4.0 International (CC BY 4.0)). …”
Section: Extraction Methods For High-value Chemicalsmentioning
confidence: 99%